Rare loss-of-function variants in type I IFN immunity genes are not associated with severe COVID-19 - Povysil, Gundula; Butler-Laporte, Guillaume; Shang, Ning; Wang, Chen; Khan, Atlas; Alaamery, Manal; Nakanishi, Tomoko; Zhou, Sirui; Forgetta, Vincenzo; Eveleigh, Robert J.M.; Bourgey, Mathieu; Aziz, Naveed; et al. (The Journal of clinical investigation, 2021)
A recent report found that rare predicted loss-of-function (pLOF) variants across 13 candidate genes in TLR3- and IRF-7 dependent type I IFN pathways explain up to 3.5% of severe COVID-19 cases. We performed whole-exome or whole genome sequencing of 1,864 COVID-19 cases (713 with severe and 1,151 with mild disease) and 15,033 ancestry- matched population controls across 4 independent COVID-19 biobanks. We tested whether rare pLOF variants in these 13 genes were associated with severe COVID-19. We identified only 1 rare pLOF mutation across these genes among 713 cases with severe COVID-19 and observed no enrichment of pLOFs in severe cases compared to population controls or mild COVID-19 cases. We found no evidence of association of rare LOF variants in the 13 candidate genes with severe COVID-19 outcomes.